A glycosyl transferase family 43 protein involved in xylan biosynthesis is associated with straw digestibility in Brachypodium distachyon - Whitehead, Caragh (The New phytologist, 2018)
© 2018 The Authors. New Phytologist © 2018 New Phytologist Trust.